Phytochemical Screening of Bioactive Compounds and Antioxidant Activity of Different Extracts From the Fruits and Barks of Ficus racemosa - Suryani, Novia; Damalianti, Yulia; Hidayanti, Baiq Rauhil; Mustariani, Baiq Ayu Aprilia; Dewi, Yuli Kusuma (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Ficus racemosa, also known as the fig plant, is renowned for its diverse medicinal properties. In light of this, our research aims to study the phytochemical compounds present in several extracts of fruits and barks of Ficus racemosa, as well as the antioxidant activity explored in the gradual solvent polarities (methanol, ethyl acetate, and hexane). The dried fruit and bark of Ficus racemosa were utilized, and extraction was obtained through successive extraction at room temperature following the cold maceration technique. Preliminary phytochemical screening of fruit and bark extracts revealed the presence of alkaloids, flavonoids, and tannins. The extracts were subjected to antioxidant activities by the 2,2-diphenyl-1-picryl-hydrazyl (DPPH) assay. Antioxidant capacity revealed the IC50 value of the methanol and ethyl acetate fruit extract of Ficus racemosa, which offered a strong capacity of 67.114 μg/mL and 69.149 μg/mL. These results indicate that the crude extract from Ficus racemosa fruit could serve as a candidate for a natural antioxidant against free radicals.